The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.35118/apjmbb.2021.029.4.07
|View full text |Cite
|
Sign up to set email alerts
|

Hibiscus sabdariffa Linn fruit derivatives as alternative agents for diabetes mellitus care: A basic insight

Abstract: This study discusses the effectiveness of methanolic extract and fractions (butanol, ethyl acetate, and n-hexane) of H. sabdariffa Linn fruit towards antidiabetic activities (in vitro). In order to test the efficacy, toxicity and insulin secretion capacity of rat pancreatic β-cell lines (BRIN-BD11) were tested with the methanolic extract and fractions. The outcomes showed that both the extract and the fractions demonstrated significantly lower levels of cytotoxic activities. Furthermore, the methanolic extract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…The aim of the work is a review of the literature describing the use of roselle in the treatment of diabetes mellitus and its accompanying diseases. Roselle has been the subject of many original and reviewed papers, including conditions that may be associated with diabetes and metabolic syndrome [ 35 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 ]. However, the existing works are older or incompletely related to diabetes, and research progress on this topic is very large [ 69 , 70 , 71 , 72 ].…”
Section: Diabetes Mellitusmentioning
confidence: 99%
See 3 more Smart Citations
“…The aim of the work is a review of the literature describing the use of roselle in the treatment of diabetes mellitus and its accompanying diseases. Roselle has been the subject of many original and reviewed papers, including conditions that may be associated with diabetes and metabolic syndrome [ 35 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 ]. However, the existing works are older or incompletely related to diabetes, and research progress on this topic is very large [ 69 , 70 , 71 , 72 ].…”
Section: Diabetes Mellitusmentioning
confidence: 99%
“…These abilities are attributed to fibroblast stimulation as well as regulation and coordination of wound vascularization by methanolic extracts from roselle fruit [ 98 ]. Also, methanolic extracts and fractions of various solvents (butanol, ethyl acetate, and n-hexane) prepared with roselle fruit were tested with regard to insulin secretion stimulation and glucose uptake [ 62 , 99 ]. The studies performed on rat pancreatic β-cell BRIN-BD11 line showed an indirect hypoglycemic effect of fruit methanolic extracts and fractions by stimulating insulin secretion in these cells, but n-hexane and butanol fractions exhibited a higher cytotoxic effect on the tested cells than methanolic extract or ethyl acetate fraction [ 62 ].…”
Section: Hibiscus Sabdariffa and Its Therapeutic Effects Stu...mentioning
confidence: 99%
See 2 more Smart Citations